Causation and Inertia over Strings - Fernando, Tim (Proceedings of the Amsterdam Colloquium, 2003)
Notions of causation and inertia in lexical and temporal semantics are studied relative to a conception of events as strings of observations (e.g. movies). Causation is defined in a temporalized forcing framework, with worlds constructed from generic sets against an inertial background of superposed strings.